Stearoyl-ACP Δ9 Desaturase 6 and 8 (GhA-SAD6 and GhD-SAD8) Are Responsible for Biosynthesis of Palmitoleic Acid Specifically in Developing Endosperm of Upland Cotton Seeds - Liu, Baoling; Sun, Yan; Xue, Jinai; Mao, Xue; Jia, Xiaoyun; Li, Runzhi (Frontiers in Plant Science, 2019)
Palmitoleic acid (16:1Δ9) is one kind of ω-7 fatty acids (ω-7 FAs) widely used in food, nutraceutical and industry. However, such high-valued ω-7 FA only has a trace level in mature seeds of cotton and other common oil crops. We found that palmitoleic acid (>10.58 Mol%) was specially enriched in developing cotton endosperm which is disappeared in its mature seed. The present study was conducted to investigate the mechanism underlying high accumulation of palmitoleic acid in developing endosperm but not in embryo of upland cotton (Gossypium hirsutum L.) seed. Of 17 stearoyl-ACP Δ9 desaturases (SAD) gene family members identified in upland cotton, six GhSADs were specifically involved the desaturation of palmitic acid (16:0-ACP) to produce palmitoleic acid (16:1Δ9-ACP), which were revealed by examining the key amino acids in the catalytic center and their cis-elements. Gene expression analysis showed that spatial patterns of these GhSADs were different in developing ovules, with GhA-SAD6 and GhD-SAD8 preferentially expressed in developing endosperms. Functional analysis by transient expression in Nicotiana benthamiana leaves and genetic complementary assay using yeast mutant BY4389 strain unable to synthesize unsaturated fatty acids demonstrated that GhA-SAD6 and GhD-SAD8 have strong substrate specificity for 16:0-ACP. In contrast, GhA-SAD5 and GhA-SAD7 exhibited high specific activity on 18:0-ACP. Taken together, these data evidence that GhA-SAD6 and GhD-SAD8 are responsible for making palmitoleic acid in developing cotton endosperms, and provide endogenous gene targets for genetic modification to enrich ω-7 FAs in cotton seed oil required for sustainable production of functionality-valued products.